KRONOSTRATIGRAFI CEKUNGAN KUTAI BAGIAN BAWAH, DAERAH BALIKPAPAN DAN SEKITARNYA, PROPINSI KALIMANTAN TIMUR - -, Yuyun Yuniardi; -, Budi Muljana; -, Rahmat Fakhrudin (Fakultas Teknik Geologi Universitas Padjadjaran, 2012)
Chronostratigraphy in lower Kutai Basin is very interesting to do research, in this area borders of chronostratigraphy need Paleontology Zone data and global tectonic. Chronostratigraphy in lower Kutai Basin divided into four part : Interval N2-N3, N4-N8, N9-N13, and N14-N21.